Cytotoxic screening and enhanced anticancer activity of Lippia alba and Clinopodium nepeta essential oils-loaded biocompatible lipid nanoparticles against lung and colon cancer cells - Rodenak-Kladniew, Boris (2023)
Plant and herbal essential oils (EOs) offer a wide range of pharmacological actions that include anticancer effects. Here, we evaluated the cytotoxic activity of EO from Lippia alba (chemotype linalool), L. alba (chemotype dihydrocarvone, LaDEO), Clinopodium nepeta (L.) Kuntze (CnEO), Eucalyptus globulus, Origanum × paniculatum, Mentha × piperita, Mentha arvensis L., and Rosmarinus officinalis L. against human lung (A549) and colon (HCT-116) cancer cells. The cells were treated with increasing EO concentrations (0–500 µL/L) for 24 h, and cytotoxic activity was assessed. LaDEO and CnEO were the most potent EOs evaluated (IC50 range, 145–275 µL/L). The gas chromatography–mass spectrometry method was used to determine their composition. Considering EO limitations as therapeutic agents (poor water solubility, volatilization, and oxidation), we evaluated whether LaDEO and CnEO encapsulation into solid lipid nanoparticles (SLN/EO) enhanced their anticancer activity. Highly stable spherical SLN/LaDEO and SLN/CnEO SLN/EO were obtained, with a mean diameter of 140–150 nm, narrow size dispersion, and Z potential around −5mV. EO encapsulation strongly increased their anticancer activity, particularly in A549 cells exposed to SLN/CnEO (IC50 = 66 µL/L CnEO). The physicochemical characterization, biosafety, and anticancer mechanisms of SLN/CnEO were also evaluated in A549 cells. SLN/CnEO containing 97 ± 1% CnEO was highly stable for up to 6 months. An increased in vitro CnEO release from SLN at an acidic pH (endolysosomal compartment) was observed. SLN/CnEO proved to be safe against blood components and non-toxic for normal WI-38 cells at therapeutic concentrations. SLN/CnEO substantially enhanced A549 cell death and cell migration inhibition compared with free CnEO.